PENINGKATAN KEMAMPUAN MEMBACA MEMINDAI SISWA MELALUI PENDEKATAN COOPERATIVE LEARNING TIPE JIGSAW II DI KELAS V SDN 02 LUBUK ALUNG - Elvi Suyarni (IICET (Indonesian Institute for Counseling, Education and Therapy), 2016)
This study originated from the reality in the field of use of the approach in learning and inadequate use of resources as well as a learning tool. This is due to the still conventional learning so that students are less interested in participating in learning, especially learning Indonesian. To the researchers interested in improving the process of learning to read scan in Indonesian language learning through the use of cooperative learning approach Jigsaw II. The aim of the PTK is to describe the improvement of reading skills of students through Jigsaw cooperative learning approach in the fifth grade II State Elementary School 02 Lubuk Alung. This type of research is the PTK (Classroom Action Research). Subjects in this study were students of class V SDN 02 Lubuk Alung. Data were obtained using a field recording, observation and evaluation (test) The results of each cycle research conducted in this study seen an increase in students' ability to read scans of the evaluation cycle I the average percentage of students ie 64%, while the evaluation of the action the second cycle the average percentage of 76%. Observations seen an increase in activity of students in the learning process. It can be concluded in this research approach is to use cooperative learning of Jigsaw II can improve students' ability to read the scan.